1995
DOI: 10.1089/end.1995.9.51
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Evaluation of Infected Renal Lithiasis: Clinical Relevance

Abstract: Complete metabolic evaluation was performed in 21 patients with infected renal lithiasis. Patients with pure struvite stones (struvite +/- carbonate apatite) were significantly less likely to have metabolic abnormalities than patients who had struvite +/- carbonate apatite+calcium oxalate (2 of 14 v 7 of 7, P = 0.0003). Urine calcium excretion was markedly higher in the mixed stone group than the pure struvite group (342 +/- 98 mg/24 h v 136 +/- 82 mg/24 h; P < 0.0001). The differing opinions among researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…22 Lingeman and associates 25 reported that only 14.2% of their pure struvite stone formers had a metabolic abnormality (hypercalciuria) whereas 100% of mixed struvite stones had abnormalities on 24-hour urine studies. In comparison, we found metabolic abnormalities (hypercalciuria, 2;…”
Section: Discussionmentioning
confidence: 99%
“…22 Lingeman and associates 25 reported that only 14.2% of their pure struvite stone formers had a metabolic abnormality (hypercalciuria) whereas 100% of mixed struvite stones had abnormalities on 24-hour urine studies. In comparison, we found metabolic abnormalities (hypercalciuria, 2;…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by the fact that a shortened urethra in females is associated with an increased risk of infection by certain pathogens, which can induce struvite (infection-related) stone formation. [25,26] Nevertheless, when we directly compared men and women with UTC, regardless of whether or not they had a history of urolithiasis, we found that men had a higher risk of developing UTC. This implied that men were exposed to more risk factors for UTC formation than women were.…”
Section: Discussionmentioning
confidence: 90%
“…This reaction neutralizes the normal negative charge of the urothelium, thereby favoring adhesion of nascent struvite crystals, and perhaps helping to accelerate crystal retention and growth of large struvite stones Clinic Rev Bone Miner Metab (2011) 9:218-228 221 treatment of the infection stone. In one series, persons with stones composed of struvite ± carbonate apatite rarely had contributing metabolic urinary abnormalities (2/14), while seven out of seven patients with stones containing calcium oxalate did [42]. In particular, urinary calcium excretion was markedly higher in the mixed stone group (349 vs. 136 mg/day) [42].…”
Section: Pathogenesis Of Infection Stonesmentioning
confidence: 98%
“…In one series, persons with stones composed of struvite ± carbonate apatite rarely had contributing metabolic urinary abnormalities (2/14), while seven out of seven patients with stones containing calcium oxalate did [42]. In particular, urinary calcium excretion was markedly higher in the mixed stone group (349 vs. 136 mg/day) [42]. The most common urease-producing bacteria implicated as causes for infection stones are Proteus, Klebsiella, Pseudomonas, and Staphylococcus species (Table 2) [43].…”
Section: Pathogenesis Of Infection Stonesmentioning
confidence: 99%